El rol del abogado como sujeto obligado a informar y su vinculación con el delito de Lavado de Activos - Beteta Amancio, Espitz (2018)
Criminal policy justifies the expansion of control over the liberties of the legal profession. It is manifested because the genesis of the crime of money laundering, leads the launderer to necessarily provide a service to transform the illicit. In that sense, there is no way to achieve a transformation of the illicit in what is said without having to resort to the legal platform.